Object-based storage. - Mesnier, M. (IEEE Communications magazine)
Storage technology has enjoyed considerable growth since the first disk drive was introduced nearly 50 years ago, in part facilitated by the slow and steady evolution of storage interfaces (SCSI and ATA/IDE). The stability of these interfaces has allowed continual advances in both storage devices and applications, without frequent changes to the standards. However, the interface ultimately determines the functionality supported by the devices, and current interfaces are holding system designers back. Storage technology has progressed to the point that a change in the device interface is needed. Object-based storage is an emerging standard designed to address this problem. In this article we describe object-based storage, stressing how it improves data sharing, security, and device intelligence. We also discuss some industry applications of object-based storage and academic research using objects as a foundation for building even more intelligent storage systems.